2014
DOI: 10.11118/actaun201159030117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of digestate and mineral fertilisers on yields and quality of kohlrabi (Brassica oleracea, L.)

Abstract: In a one-year vegetation pot experiment we compared the effect of the digestate from a biogas station and mineral fertilisers on yield and quality parameters of kohlrabi, variety Seguza. Four treatments were used in the trial: 1) untreated control, 2) urea, 3) digestate, 4) urea, triple super phosphate, KCl, MgSO4. The rate of N was the same in treatments 2–4, 1.5 g N/pot. In treatment 4 the rate of P, K and Mg corresponded with the rate of these nutrients in the digestate treatment (3). The weight of single b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…There was thus an obvious positive synergistic effect of additional nutrients in digestates (especially N and K) on yields. This confirms that N is the decisive element in terms of yields as reported previously by Feller and Fink (1997) and Lošák et al (2011). In experiments lasting several years Stinner et al (2008) also reported positive effects of three different types of digestate (fermented clover-grass mixture, cover crops and post-harvest residues) on wheat yields.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…There was thus an obvious positive synergistic effect of additional nutrients in digestates (especially N and K) on yields. This confirms that N is the decisive element in terms of yields as reported previously by Feller and Fink (1997) and Lošák et al (2011). In experiments lasting several years Stinner et al (2008) also reported positive effects of three different types of digestate (fermented clover-grass mixture, cover crops and post-harvest residues) on wheat yields.…”
Section: Resultssupporting
confidence: 75%
“…However, in a previous experiment with kohlrabi of the cv. Segura F1 (Lošák et al 2011) the content of ascorbic acid was found to be higher in all the fertilised treatments (772-789 mg/kg FM) as compared to the unfertilised treatment (511 mg/kg FM). Previous studies differ in their conclusions regarding the effect of nitrogenous fertilisation on the content of vitamin C. Mozafar (1993) reported Mean values of kohlrabi bulb nitrates (n = 4).…”
mentioning
confidence: 97%
See 3 more Smart Citations